The space-time approach to rail/wheel contact and corrugations problem - Bajer, Czesław I. (Computer Assisted Methods in Engineering and Science, 2023)
The paper presents a space-time discrete modeling of the dynamic rail-wheel contact problem and an analysis of the induced corrugations. First, the space-time approach to simple contact problems is presented.Then, the resulting differential equation of motion is solved by discrete time integration. An arbitrary mesh modification, both in time and space, enables an easy modeling of rapidly varying contact zone. The velocity formulation is used and the discontinuity of the velocity in the contact is removed by a special algorithm. Finally the discussed technique is used to simulate interaction of the elastic wheel and rigid rail. It is shown that the contact force oscillates and the material of the wheel rotates oscillatory.